Dietary supplementation with antibacterial peptide microcin J25 improved antioxidant capacity and intestinal health of pigeons - Cao, Heng; Lu, Yinglin; Zhang, Xingyu; Li, Fan; Li, Ming; Zhou, Jing; He, Huiting; Ma, Qing; Yu, Minli (Frontiers in Veterinary Science, 2025)
IntroductionThe present study aimed to evaluate the potential of antimicrobial peptide microcin J25 (MccJ25) as a feed additive for pigeons.MethodsA total of 28-day-old pigeons were allocated to four groups and fed a basal diet (CON) or a basal diet supplemented with 100, 200, or 300 mg/kg MccJ25 (ABP100, ABP200, and ABP300) for 8 weeks.ResultsDietary MccJ25 supplementation significantly improved survival rates in the ABP200 group compared to the control (p < 0.05). Serum analysis revealed that ABP200 and ABP300 groups exhibited increased levels of total protein (TP), globulin (GLB), immunoglobulin A (IgA), and immunoglobulin G (IgG), alongside reduced aspartate aminotransferase (AST), alanine aminotransferase (ALT), total cholesterol (TC), and triglyceride (TG) concentrations (p < 0.05). Furthermore, MccJ25 supplementation enhanced duodenal maltase and trypsin activity (p < 0.05) and upregulated intestinal and hepatic antioxidant capacity, as evidenced by elevated glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) activity (p < 0.05). Intestinal morphology improvements were observed in the jejunum and ileum, with increased villus height-to-crypt depth ratios (VH/CD) (p < 0.05). Additionally, ABP200 and ABP300 groups demonstrated significant upregulation of intestinal barrier-related genes occludin (OCLN), claudin 1 (CLDN1), zonula occluden protein 1 (ZO1), mucin 2 (MUC2), superoxide dismutase 1, 2 (SOD1, 2), and catalase (CAT) in duodenum (p < 0.05).DiscussionThese findings indicate that MccJ25 supplementation improves systemic metabolism, enhances antioxidant defenses, strengthens intestinal barrier integrity, and ultimately promotes pigeon health and survival. This study supports the application of MccJ25 as a functional feed additive in poultry production.